Scope of the Simplified Joint Stock Company in the light of the contractual freedom principle in corporate law - Ortiz Cano, María Isabel; Ortiz Cano, María Isabel; Ortiz Cano, María Isabel (Corporación Universitaria Americana, 2020)
This article analyzes the legal incentives and obstacles included in the Law 1258/2008 which regulates the Simplified Joint Stock Company type in the colombian legal system. Given the fact that there are a lot of subsidiary rules and very few imperative rules in this Law, allowing the shareholders to create their own rules. For this reason the text contrasts the Simplified Joint Stock Company regulation with the rules of other companies typified in the Colombian Commercial Code, regarding the principle of contractual freedom and its historical development in the corporate law. Furthermore, the text measures the overall scope of the Simplified Joint Stock Company type in the colombian legal system within more than a decade of its existence.